2011
DOI: 10.1007/s10571-011-9737-7
|View full text |Cite
|
Sign up to set email alerts
|

The Striatum and Pain Modulation

Abstract: The aim of this review was to give a general aspect of the sensorial function of the striatum related to pain modulation, which was intensively studied in our laboratory. We analyse the effect of electrical and chemical stimulation of the striatum on the orofacial pain, especially that produced by tooth pulp stimulation of the lower incisors. We demonstrated specific sites within the nucleus which electrical or chemical stimulation produced inhibition of the nociceptive jaw opening reflex. This analgesic actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 84 publications
8
43
0
Order By: Relevance
“…Both the striatum and hippocampus have been heavily implicated as CNS regions involved in pain processing and perception (Malow and Olson, 1981; Mcewen, 2001; Ploghaus et al, 2001; Ferre et al, 2009; Barcelo et al, 2012), and our study confirms that there are changes in the production of these putative N -acyl amide signaling molecules in the striatum and hippocampus due to inflammatory pain. However, one of the major limitations of this study is the heterogeneity of these brain areas.…”
Section: Discussionsupporting
confidence: 81%
“…Both the striatum and hippocampus have been heavily implicated as CNS regions involved in pain processing and perception (Malow and Olson, 1981; Mcewen, 2001; Ploghaus et al, 2001; Ferre et al, 2009; Barcelo et al, 2012), and our study confirms that there are changes in the production of these putative N -acyl amide signaling molecules in the striatum and hippocampus due to inflammatory pain. However, one of the major limitations of this study is the heterogeneity of these brain areas.…”
Section: Discussionsupporting
confidence: 81%
“…Thus the DRt is strategically positioned among the extrapyramidal and pain descending systems, indicating a possible involvement in the motor reaction to pain. It has been also recently reported that RVM mediates the analgesic action of the striatum: lesion of RVM blocked the inhibition control of striatum on orofacial pain (Barceló et al 2012). Evidence that stimulation of striatum leads to pain reflex inhibition (Belforte et al 2001) through RVM, however, has been scarcely investigated so far (Barceló et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also recently reported that RVM mediates the analgesic action of the striatum: lesion of RVM blocked the inhibition control of striatum on orofacial pain (Barceló et al 2012). Evidence that stimulation of striatum leads to pain reflex inhibition (Belforte et al 2001) through RVM, however, has been scarcely investigated so far (Barceló et al 2012). Within the RVM, ON cells are activated by nociceptive stimuli and have a pain facilitatory effect (Fields et al 1983), whereas OFF cells are inactivated and have an inhibitory effect on nociception (Fields et al 1983(Fields et al , 2006Heinricher and Tortorici 1994;Kincaid et al 2006;Neubert et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations